Przyjemność lektury - Bulanowski, Marek Oktawian (Przestrzenie Teorii, 2014)
Henryk Markiewicz’s book Czytanie Irzykowskiego [Readings of Irzykowski] is a collection of studies dedicated to the work of a leading Polish modernist critic who was also an influential theorist, historian of literature and author of the experimental novel titled Pałuba. Although this collection does not constitute a monograph on Karol Irzykowski’s work, the variety of methodological approaches that are presented in the articles reveals Markiewicz’s characteristic interests and shows that contemporary literary studies focus on reading and history rather than theory (P. de Man). These studies were influenced by the ideas of Russian formalists (B. Eichenbaum), semiotics and Marxism; however, Markiewicz does not faithfully adhere to any methodological school. Above all, his studies show that he is interested in literariness, literary works of art, the history of ideas and correct interpretation.